The Relationship Between E-Cadherin and its Transcriptional Repressors in Spontaneously Arising Canine Invasive Micropapillary Mammary Carcinoma. Issue 4 (November 2015) - Gamba, C.O.; Rodrigues, M.A.; Gomes, D.A.; Estrela-Lima, A.; Ferreira, E.; Cassali, G.D.
Summary: E-cadherin downregulation is related to metastatic behaviour and a poor prognosis in cancer. It might be induced by transcriptional repression mediated by the transcription factors SNAIL, ZEB1, ZEB2 and TWIST. Here, we investigated E-cadherin expression and its relationship to those transcriptional repressors (i.e. SNAIL, ZEB1, ZEB2 and TWIST) in the progression from carcinoma 'in situ' to invasion to lymph node metastasis in spontaneously arising canine invasive micropapillary carcinoma (IMPC). E-cadherin expression decreased from carcinoma in situ to invasive progression and was likely to increase with lymph node metastasis. Expression of SNAIL decreased from carcinoma in situ to invasive areas and from invasive areas to lymph nodes. Metastatic lymph nodes had higher expression of ZEB1 than carcinoma in situ and invasive areas. ZEB2 expression was observed in 52%, 38% and 33% of carcinoma in situ areas, invasive areas and lymph node metastases, respectively. TWIST expression was observed in 52%, 38% and 33% of carcinoma in situ areas, invasive areas and lymph node metastases, respectively. In invasive areas, E-cadherin downregulation correlated significantly with SNAIL and TWIST upregulation. Additionally, in infiltrating components of IMPCs, E-cadherin − SNAIL + neoplastic epithelial cells were observed by immunofluorescence. Taken together, canine mammary IMPCs had a loss of E-cadherin from carcinoma in situ to invasive areas, which appears to be induced by the transcription factor SNAIL. In lymph node metastasis, ZEB1 appears to not exert E-cadherin transcriptional repression activity.